Professionalism of Accountants in the Digital Era: Ethics, Competence, and Public Trust - Adriansyah; Rais, Anisatun Humayrah; Windarsari, Wiwin Riski (Review of Accounting and Business, 2025)
Introduction/Main Objectives: This paper examines the professionalism of accountants and its role in sustaining public trust in the digital era. Professionalism is viewed not only as technical competence but as a multidimensional construct shaped by ethics, expertise, and adaptability to technological transformation. Background Problems: Accounting scandals, both globally and in Indonesia, have eroded confidence in the profession. Meanwhile, rapid digitalization introduces new risks and ethical challenges, raising questions about whether traditional codes of ethics adequately address issues such as data privacy, algorithmic bias, and cyber fraud. Novelty: This study integrates ethical, technical, and digital aspects into a comprehensive framework of professionalism. The Indonesian context illustrates how cultural values and uneven digital readiness influence professional conduct. Research Methods: A qualitative literature review was conducted using academic journals, professional codes of ethics, and regulatory documents. Content analysis identified recurring themes across ethics, competence, and digital literacy. No primary data were collected, as the research relied entirely on secondary sources. Findings/Results: The findings show that professionalism is multidimensional, combining ethical integrity, technical skill, and digital adaptability. Accountants engaged in continuous learning and digital upskilling are more capable of preventing fraud, ensuring compliance, and maintaining credibility. However, disparities in training and infrastructure in Indonesia limit consistent professional quality. Conclusion: Professionalism in the digital era requires balancing ethics, competence, and digital proficiency. Future studies should employ bibliometric or empirical methods to validate the conceptual relationships proposed.